ANALISIS KUALITAS RANCANGAN USER INTERFACE DAN USER EXPERIENCE PADA APLIKASI BCA MOBILE MENGGUNAKAN METODE UEQ - Iskandar, Aliah (JUPIK : Jurnal Penelitian Ilmu komputer, 2024)
The role of User Interface (UI) / User Experience (UX) is very important in a company, especially web and application based companies. UI/UX can be a good long-term investment for a company. BCA is a company in the banking sector that has many mobile banking applications. One of them is the BCA Mobile application. This research involved 137 users who filled out a questionnaire. The aim of this research is to make the appearance of the application and user experience in using the BCA Mobile application better and more enjoyable. It is hoped that the UEQ (User Experience Questionnaire) method can help in completing this research. The results of the user experience evaluation on the BCA Mobile application using the UEQ method stated that the attractiveness aspect was 1.90, the clarity aspect was 2.68, the efficiency aspect was 1.91, the accuracy aspect was 1.80, the stimulation aspect was 1.70, and the novelty aspect is 1.68. This proves that all aspects have positive value. The benchmark results show that the attractiveness, visibility, efficiency and stimulation aspects are included in the very good criteria. The clarity aspect got the highest score and the novelty aspect got the lowest score in this research.